Development of al-Qawaid an-Nahwiyah Learning Module Based on Qiyasiyah Method for Arabic Language Education Department Students | Pengembangan Modul Pembelajaran al-Qawaid an-Nahwiyah Berbasis Metode Qiyasiyah untuk Mahasiswa Jurusan Pendidikan Bahasa Arab - Saiful Anwar; Guntur Cahaya Kesuma; Koderi (Mantiqu Tayr: Journal of Arabic Language, 2023)
The development of the al-qawaid al-nahwiyah learning module based on qiyasiyah method for students majoring in Arabic Language Education to find out the steps in developing the al-qawaid an-nahwiyah module using the qiyasiyah method and to determine its feasibility and effectiveness. This module is structured based on research and development methods using the ASSURE model with six research steps. This study produced an interesting al-qawaid al-nahwiyah learning module based on qiyasiyah method starting from content, content and evaluation accompanied by general structures, pictures and appropriate coloring. This module is very effective for use in learning nahwu for students majoring in Arabic Language Education because has been tested from the results of trials that have been conducted by researchers and is a solution to difficulties in understanding nahwu science through literature printed in Arabic. Student learning outcomes can be seen in the pretest scores obtained by an average value of 56 and the average posttest value of 78.6. Based on the results of the T-Test analysis carried out with a truth level of 95%, it can be concluded that the learning outcomes of students in the al-qawaid al-nahwiyah course with the al-qawaid al-nahwiyah learning module based on the qiyasiyyah method have significant differences, meaning that learning outcomes students before and after using the al-qawaid al-nahwiyah learning module based on the qiyasiyyah method there are positive differences.